Child with Choledochal Cyst Presenting with Episodes of Vomitting and Jaundice - Santos, R (2009)
A 2 year old girl presented to the emergency department with frequent episodes of vomiting and jaundice. Analytically, there was leucocytosis with normal neutrophil count, RCP of 5, 66 mg/dL and GGT 87 U/L. Colluria was also found.